Printing protection package for medicine - Бизюк, Андрей Валерьевич; Воронина, Алина Александровна (Eastern-European Journal of Enterprise Technologies, 2012)
In this work discusses the methods and ways to protect the printed packaging of medicines from counterfeits. The requirements for packaging for medicine are clarified